SYNERGISING INTERNATIONAL LABOUR LAWS AND HUMAN RIGHTS FOR PROTECTION OF INDONESIAN MIGRANT WORKERS - Muhammad Abdul Azis; Muhammad Syaprin Zahidi; David Pradhan (Faculty of Law Universitas Lampung, 2020)
Efforts in promoting international legal protection of Indonesian migrant workers can be explained that it has complete regulations. This situation cannot be separated from the facts that show the importance of granting Specific labour rights for migrant workers in the international community’s perspective. The purposes of this article are to encourage all people to consider seriously the applying of international human rights law in order to promote of human rights, especially, for Indonesia migrant workers (TKI) and create better migration management. In legal-formal matter, the applying of legal mechanisms has been recognized as human rights by Indonesia law. One of the best ways is trying to join the outside world in order to attain Economic development for the nation. Exploiting Opportunities of globalized world economy does not mean our sovereignty weakened but rather as an effort to achieve more substantive effort. This can be interpreted as a political commitment from the government - by learning and cooperating with Other States - to be more pragmatic by prioritizing the interests of the people as a form of democracy.